Effect of gamma-rays on recombination dynamics and defect concentration in a wide bandgap perovskite - Aleksandra G. Boldyreva; Marina M. Tepliakova; Artyom V. Novikov; Vladimir G. Petrov; Olga Parfenova; Alexander A. Golubnichiy; Anton Vasilev; Danila Saranin; Keith J. Stevenson (Light: Advanced Manufacturing)
Herein, we have explored the recombination dynamics and defect concentration of a mixed cation mixed halide perovskite Cs0.17FA0.83PbI1.8Br1.2 with 1.75 eV bandgap after exposure to a gamma-ray source (2.5 Gy/min). We used photoluminescent spectroscopy to observe changes in recombination dynamics on perovskite films, impedance spectroscopy to reveal the contribution of interface recombination, and admittance spectroscopy to define the activation energy and concentration of defects. It was revealed that moderate doses (up to 10 kGy) passivate defects with activation energy ≈ 0.5 eV and at the same time form new defects that cause dramatic growth of the diffusion coefficient and migration of mobile ions. These two processes with opposite direction result in high radiation tolerance of the studied material and solar cells up to 10 kGy. Doses above 10 kGy are detrimental for perovskite solar cells, mainly due to the growing role of interface recombination. The results encourage the use of the wide bandgap perovskite Cs0.17FA0.83PbI1.8Br1.2 as a material for tandem solar cells with potential applications in a space environment.